Development of History E-Modules: Book Creator Application as a Learning Innovation in the Era of Independent Learning - Dini Wariastuti; Abdul Hamid K; Samsidar Tanjung (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to produce E-module products, analyze the feasibility of E-modules, analyze the practicality of E-modules, and determine the effectiveness of E-modules. Research and development methodology uses the ADDIE model, which consists of stages: analysis, design, development, implementation, and evaluation. Development of the E Module using Book Creator on the history subject of the independent era studied at SMAS Panca Budi Medan. The research results show: Based on the results of material expert validity tests, the E Module using Book Creator in the History of the Independent Learning Era subject is very suitable for use with an average gain of 90.7%; the results of the media expert validity test, E Module using Book Creator in the History subject, are very feasible with an average score of 93.1%; the design expert's validity test results were very feasible with a score of 86%; Based on experiments conducted in the experimental class, where learning used the E Module, the average student learning outcome was 92.93; and the results of the T and N-Gain Score tests on the learning outcomes of experimental class students show that the E Module is effectively used in history learning, where the average gain of the N-Gain Score test is 83.33%, and based on the Independent Samples Test, Sig is obtained. . (2-tailed) of 0.001, where 0.001 < 0.05